Analysis of Teacher Perceptions of Online Gamification Learning Methods - Putra, Hamda Kharisma; Ekosusilo, Madyo; Subiyantoro, Singgih; Ismail, Ismail; Fauziyah, Syifa (Edutech Publishing Media, 2024)
The integration of gamification into online learning has garnered considerable attention in contemporary educational discourse. This article delves into teachers' perceptions regarding the implementation of this method. The background lies in the increasing utilization of technology in education and the potential of gamification to enhance student engagement and motivation. The objective is to explore teachers' viewpoints on the effectiveness, challenges, and benefits of this learning method. The research methodology involves surveys and interviews with a cohort of teachers who have utilized gamification in their online teaching practices. Findings reveal a spectrum of perceptions among teachers, including their understanding of gamification concepts, comfort levels in its application, and its influence on student engagement. The conclusion drawn highlights positive acceptance of gamification, alongside identified challenges such as time constraints and technical skills. The research contributes valuable insights for the development and implementation of gamification learning methods in the online education landscape.